Allergen characterization in childhood asthma: a retrospective cohort study in China - Hu, Chong; Dong, Qin; Zhang, Yanzi; Wang, Juan; Wu, Dan; Lv, Xin (Frontiers in Public Health, 2025)
BackgroundThe increasing cases of asthma in children around the world necessitate the profiling of regional specific allergens to manage it precisely. This research study identifies the sensitization patterns of Chinese children with asthma and the necessity of its undertaking for the prevention of this chronic respiratory illness that is prevalent in children.MethodsWe selected and included 6,785 pediatric patients with a clinical diagnosis of bronchial asthma at the Children’s Hospital Affiliated to Shandong University from January 2018 to January 2025 with the cohort study design. Serum specific IgE (sIgE) was tested in all patients for 19 types of inhalant and food allergens.ResultsIn this study, house dust mites (HDMs) (52.99%) had the highest positive rate of, followed by molds (31.98%) and dog dander (28.17%). Food allergens that had the highest positive rates were egg white (32.45%), milk (19.96%) and beef (16.32%). The positive rate of the food allergens was higher in the 0–1 year-old group and the 1–3 year-old group compared to the inhaled allergens. On the other hand, inhaled allergens were more frequently positive than food allergens among children aged 3 to 6 years, 6 to 12 years, and over 12 years, with some of the differences being statistically significant. The positive rates of inhaled allergens were higher than those of food allergens in all months in terms of monthly distribution. Multi-allergen sensitization, in particular, the linking of HDMs with other allergens, was the most common sensitization profile identified in this study.ConclusionThe results of this study will be of great use in the transformation of experience-based diagnosis and treatment of childhood asthma into a standardized and personalized model on the basis of precise distribution of allergen. The change will reduce the occurrence of asthma attacks, enhance the quality of life of children and have much practical and clinical significance associated with the enhancement of the prevention and treatment of childhood asthma in the region.